Understanding the Technicalities of Photorealistic 3D Environments to Support Cinematography and Composition for Film and Animation - Joon, Jong Sze; Hui, Soon Eu; Chan, Yuen May (2008)
This paper reviews the integration of Computer Graphics principles in simulating photorealistic 3D environments integrating life action footage for film. To achieve adequate believability and create impact, the look of the 3D background requires digital enhancement to achieve a certain stage of realism. This will depend primarily on the material/shader and renderer utilised in the 3D application. Despite having the realistic look, the other aspect to consider for a perfect merge between 3D and life requires one to skillfully match perspective and lighting. Another aspect to consider is the cinematography and composition of the scene.